Pengaruh Kredit Usaha Rakyat (KUR) Terhadap Pendapatan Usaha Pada UMKM - Wani, Ega (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2023)
The problem that is often faced by every UMKM is inseparable from the need for funds to finance their business. To meet their needs, almost all UMKM use their own capital besides that through banks which are often known as People's Business Credit (KUR). People's Business Credit Loans are one way and also an alternative that is usually used by business owners ranging from large, medium and even small businesses, which applies when you don't have enough capital to create a new business or develop an existing business.